Underlying behavioural and physiological determinants of dominance hierarchy in a eusocial mammalian species, the naked mole-rats (Heterocephalus glaber) - Bennett, Nigel Charles (University of Pretoria, 2023)
Thesis (PhD (Zoology))--University of Pretoria, 2023.